Conflict of Norms in Public International Law : How WTO Law Relates to other Rules of International Law - Pauwelyn Joost (Cambridge University Press, 2003)
How do trade agreements interact with agreements on human rights or the environment? In case of conflict, which agreement should prevail? Pauwelyn considers these questions here, providing a framework for how the different rules of international law interact, and procedural guidelines in the event of conflict between them.